Biofertilizantes como reatores em grânulo: sistemas carreadores com Aspergillus niger e Trichoderma asperelloides para ações no controle biológico, promoção do crescimento de plantas e solubilização de fósforo - Favaro, Camila Patrícia (Universidade Federal de São Carlos, 2021)
In recent years, the importance of microorganisms role in maintaining agricultural productivity has been highlighted, being essential in cycling nutrients and production of metabolites to contribute to plant growth and protection. All these factors contribute to growth of biological products market. However, studies are still needed to improve and develop production technologies and maintain the quality of these products. Associating the use of unprocessed phosphate rocks (PR) with the microbial P solubilization, we developed a process to produce a biofertilizer granule from cold extrusion, capable of scaling. The granule acts as a micro reactor, where the nutrient of formulation supports microorganism growth for production of metabolites capable of solubilizing the phosphorus (P) of rock, biological control, and plant growth promotion. In the first stage of this work, the P solubilization have been evaluated by Aspergillus niger and Trichoderma spp. isolated and combined in submerged cultivation, using different phosphate rocks powder. At this stage, the strains, and the PR to be used in the development of the granule were selected. The production of the biofertilizer granules process was developed, with the isolated and combined strains. In the biofertilizer granule, an increase of up to 150% in the solubilization of P was observed when compared to the cultures with phosphate rock powder. The antagonism in vitro of the biofertilizer with Fusarium oxysporum demonstrated the capacity of T. asperelloides for biological control. The combination with A. niger did not affect its performance of T. asperelloides. Subsequently, aiming to reduce the production costs of biofertilizers granules and reduce the waste generation, the substrate for microorganisms cultivation (rice grains) was used as a nutrient source in formulation. The viability of the formulations in storage at 4 °C and room temperature was evaluated, showing the importance of studying the storage conditions to maintain the quality of the product. Finally, the biofertilizer granules with isolated and combined microorganisms were evaluated in a soil-plant system (rhizotron), analyzing root and plant growth of tomato, and the dynamics of P in soil. The presence of T. asperelloides promote statistically significant differences in plant height. The presence of A. niger generated an increase in P in the fractions that showed greater migration dynamics of this component to the more labile fractions. These results which demonstrated the potential applicability of the product. The production process developed of biofertilizer granule by cold extrusion opens new doors for use of different carrier materials and the development of new granular biological products for direct application in agriculture.
Biofertilizers as granule reactors: carrier systems with Aspergillus niger and Trichoderma asperelloides for biological control, plant growth promotion and phosphorus solubilization
Keywords: Trichoderma asperelloides; Aspergillus niger; Produtos biológicos; Controle biológico; Consórcio de microrganismos; Rocha fosfática; Biological products; Biological control; Microbial consortium; Phosphate rock; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA